The just war revisited - O'Donovan, Oliver (Current issues in theology, 2003)
Leading political theologian Oliver O'Donovan takes a fresh look at some traditional moral arguments about war. Christians differ widely on this issue. The book re-examines questions of contemporary urgency, including the use of biological and nuclear weapons, military intervention, economic sanctions, war-crimes trials, and the role of the UN.